2013
DOI: 10.1021/es401265q
|View full text |Cite
|
Sign up to set email alerts
|

Toxicogenomic Responses of Zebrafish Embryos/Larvae to Tris(1,3-dichloro-2-propyl) Phosphate (TDCPP) Reveal Possible Molecular Mechanisms of Developmental Toxicity

Abstract: Tris(1,3-dichloro-2-propyl) phosphate (TDCPP) is frequently present in indoor dust and can be detected in human milk. In order to evaluate the effects of TDCPP on vertebrate development, zebrafish embryos/larvae were used as an animal model to examine developmental phenotypes and explore possible mechanisms of toxicity by employing microarrays and iTRAQ labeling quantitative proteomics. The results demonstrated that treatment with TDCPP (3 μM) from 0.75 h postfertilization (hpf) inhibited cell rearrangement at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 105 publications
(67 citation statements)
references
References 34 publications
4
63
0
Order By: Relevance
“…The recovery of extraction of TBEP was 84.15%. For the quantification of TBEP in zebrafish larvae, the analysis was conducted according to a previously published protocol for TDCPP (Fu et al, 2013), using a Waters ACQUITY UPLC system equipped with a Waters ACQUITY triple quadrupole mass spectrometer (Waters, Milford, MA, USA). Briefly, zebrafish larvae were freeze-dried, homogenized and ground with diatomaceous earth.…”
Section: Quantification Of Tbep In Exposure Solutions and Zebrafish Lmentioning
confidence: 99%
See 3 more Smart Citations
“…The recovery of extraction of TBEP was 84.15%. For the quantification of TBEP in zebrafish larvae, the analysis was conducted according to a previously published protocol for TDCPP (Fu et al, 2013), using a Waters ACQUITY UPLC system equipped with a Waters ACQUITY triple quadrupole mass spectrometer (Waters, Milford, MA, USA). Briefly, zebrafish larvae were freeze-dried, homogenized and ground with diatomaceous earth.…”
Section: Quantification Of Tbep In Exposure Solutions and Zebrafish Lmentioning
confidence: 99%
“…Quantitative proteomic analysis was conducted according to previously published methods (Fu et al, 2013). Peptide identification was performed using the following parameters: Cys alkylation: MMT(C), ID focus: biological modification, Digestion: trypsin, Database: zebrafish, Search effort: thorough ID, unused protein score >1.3 (>95% confidence).…”
Section: Quantitative Proteomic Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…These data more comprehensively and quantitatively described changes in morphology during development of larvae exposed to chemicals. In this study, it was determined that exposure to 0.1 or 0.2 mg/L TDCIPP significantly altered lengths of more than 50 lines or angles, while studies using the traditional methods of microscopic examination found no significant malformations due to exposure of zebrafish to concentrations of TDCIPP 0.2 mg/L (McGee et al, 2012;Fu et al, 2013). These results suggest that the three-step method developed during this study is more sensitive than previous methods based on more limited observations through the microscope.…”
Section: Discussionmentioning
confidence: 91%